신문을 활용한 회상 프로그램이 알츠하이머형 치매인의 언어이해력에 미치는 효과 - 이성호(Soung-Ho Lee); 강수균(Soo-Kyoon Kang); 손은남(Eun-Nam Sohn) (언어치료연구, 2007)
이 연구는 신문을 활용한 회상프로그램이 알츠하이머형 치매 노인의 언어이해력에 미치는 효과를 알아보고자 하였다. 연구 대상자는 전문의로부터 알츠하이머형 치매로 진단받았고, K-MMSE의 점수가 23점 이상이며, K-DRS의 진단에서 -2표준편차에 위치함으로써 ‘인지 이상’ 소견을 보이는 65세 이상 노인 3명으로 구성되었다. 중재의 효과를 사전 사후에 검사하는 실험 설계를 하였으며, 중간 평가를 5회기마다 실시하였다. 신문을 이용한 프로그램 주제는 대상자들의 연령을 고려하여 경험한 것, 주변에서 자주 듣고 볼 수 있는 친근한 소재 및 관심거리를 중심으로 선정하였다. 연구 결과에 따르면, 신문에 대한 친숙함과 대상자들에게 관심 있는 주제를 선정한 결과 재인 회상을 통한 이야기 회상하기에서 기억 기능의 활성화가 이루어졌다. 그와 함께 인지 능력을 향상시켜 언어적 이해력에 효과가 있으므로 타인과의 의사소통 능력이 향상 될 수 있었다. The primary purpose of this study was to investigate the effect of language comprehension by using news stories. This study consists of three subjects, who are diagnosed with dementia (a kind of Alzheimer's Disease), K-MMSE: 23 points, K-DRS:2 standard deviation. All subjects were over sixty-five years old and diagnosed with a mental disability. Thirty sessions were performed, for thirty minutes, two times a week. We made an experiment that would check the effect, before and after testing. Subjects are considered dementia patients, so they were assessed every 5 sessions. We kept the experiment basic, and the rules regarding the subjects during treatment. The data that the researchers gathered was put to use. We chose the treatment for the subject to be involve natural things that we usually see and listen to. We used the newspaper of part of the experiment. According to the results, they were able to recall stories through recognition. This caused the memory ability to become active, and improved intelligence ability, it also improved their comprehension of language. They could understand the effect much better than before the treatment. Patients explained the story, after they looked at improved. We chose subjects that old people are familiar with, also their favorites from the newspaper. KCI Citation Count: 7